PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN RITEL - Siti Nuridah; Joelianti Dwi Supraptiningsih; Sopian Sopian; Mutiara Indah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine how much influence Profitability and Company Size have on Capital Structure in Retail companies listed on the Indonesian Stock Exchange for the 2019-2021 period. The data analysis method in this study is the associative analysis method and the quantitative analysis method. The population in this study are retail companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Purposive sampling was chosen as the sampling technique. The samples used in this study amounted to 10 companies. Simultaneous results that Profitability and Firm Size jointly affect the Capital Structure. Furthermore, for partial testing or called the t test, the Profitability variable has a negative and significant effect on Capital Structure. As well as the variable Company Size partially has a negative and significant effect on Capital Structure. Profitability and company size variables have a contribution of 41.2% while the remaining 58.8% is influenced by other factors.